Can prestin level be a biomarker for determining sensorineural hearing loss? - Emre, Sadettin; Karlidag, Turgut; Aydinb, Sueleyman; Kaygusuz, Irfan; Keles, Erol; Akyigit, Abdulvahap; Yalcin, Sinasi (Elsevier Sci Ltd, 2022)
Objective: To determine prestin levels in patients with sensorineural hearing loss and to assess whether the prestin level could be a determining factor in predicting sensorineural hearing loss. Material and methods: The study was carried out with patients that presented to the Department of Otorhinolaryngology of Firat University. Patients were divided into four groups of 30 subjects. Group 1: individuals aged >= 55 years with no hearing loss (control group); Group 2: individuals aged 20 to 55 years with no hearing loss (control group); Group 3: individuals aged 20 to 55 years with sensorineural hearing loss; Group 4: individuals aged =55 years with presbycusis. Following an audiometry examination, 5 cc blood was taken from all patients to assess serum prestin levels. Results: Prestin levels were 445.32 pg/mL in Group 1; 452.79 pg/mL in Group 2; 123.64 pg/mL in Group 3; and 79.54 pg/mL in Group 4. No difference was found between the serum prestin levels of the younger patients with hearing loss (Group 3)] and of the patients with presbycusis (Group 4) (p=0.084). No difference was found between the serum prestin levels of the younger (Group 1) and the older (Group 2) patients with presbycusis (p=0.399). Significant differences (with higher levels in the control groups) were found in between the prestin levels of between Group 3 (the younger patients with sensorineural hearing loss) and Group 2 (younger controls), and between Group 4 (older patients with presbycusis) and Group 1 (older controls) (p <0.001 and p <0.001, respectively). Conclusion: Serum prestin levels can be used as biomarkers for assessing patients with presbycusis and sensorineural hearing loss. They can also be used together with audiometry tests to predict the patient's potential level of hearing loss. (C) 2021 Japanese Society of Otorhinolaryngology-Head and Neck Surgery, Inc. Published by Elsevier B.V. All rights reserved.
Keywords: Prestin; Presbycusis; Hearing loss